Extensive venous thrombosis in a runner: Progression of symptoms key to diagnosis - Fleming, A.; Frey, D. (The Physician and Sportsmedicine, 2005)
Although usually considered a disease of sedentary people, deep venous thrombosis can occur in active patients. Physical findings may be difficult to differentiate from those of muscle trauma, a Baker's cyst, or hematoma. A high index of suspicion must be maintained, because delay in making the diagnosis and initiating anticoagulation may have fatal consequences. Doppler flow studies are required in all cases of limb pain or swelling in runners when deep venous thrombosis is even remotely suspected, as in this case of a 40-year-old man who developed ankle and lower-leg pain 1 month after a 10-km run. If promptly treated, patients can make a safe return to training without adverse consequences.